Hubungan Panjang Berat dan Kondisi Habitat pada Dua Spesies Catfish di Sungai Barumun Kabupaten Labuhanbatu - Khairul, Khairul (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Catfish is a demersal fish inhabiting the waters of the River. There are two species that are often caught in the Barumun River: the blacktip sea catfish (Piicofillis dussumieri Valenciennes, 1840) and the grey eel catfish (Plotosus canius Bleeker, 1858). Both of these species have economic value that is quite important for the coastal communities of Labuhanbatu Regency. Fishing gear used to take samples of fish in the form of: trap, gill nets, and fishing rods. All fish caught were then measured in total length using a ruler and their weight using analytical scales. Analysis of research data using the Linear Allometric Model (LAM) equation. Based on the results of the study the length relationship of blacktip sea catfish weight obtained values b = 32,38 and R2 = 0.95 and grey eel catfish obtained values b = 2,56 and R2 = 0.26. It was concluded that the long relationship ofblacktip sea catfish weight is allometric positive and grey eel catfish is allometric negative. The results of observations of water quality parameters for temperature (29-30ºC), brightness (0.5 – 0.8 m), current speed (0.8 – 0.9 m/s), salinity (5.1 - 15.3 ‰), pH (6), and dissolved oxygen (6.9 – 7.2 mg/L) and habitat conditions of both catfish species are still in accordance with quality standards for river waters.